KOMUNIKASI PERSUASIF PT. PEGADAIAN (PERSERO) DALAM MENINGKATKAN JUMLAH NASABAH TABUNGAN EMAS, CABANG PANAM KOTA PEKANBARU PROVINSI RIAU - Valentini, Nurisya; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Gold is one asset because gold has a value that tends to be stable even will give advantage in time. Therefore some people make gold as a means to save.PT. Pegadaian (Persero) is one of the state-owned companies in Indonesia. The success of PT. Pegadaian can be seen from the many branches of each region in Indonesia and various product service programs that have been launched the PT. Pegadaian, one of which is gold saving. This program invites people to learn to invest where the investment is done by saving based on the provisions of at least Rp.5.000,00 then the customer has been getting gold.PT. Pegadaian (Persero) is usually synonymous with service to the community, especially the middle class down, therefore, the gold savings that issued PT. Pegadaian (Persero) is a program that is addressed to the lower middle class. However, over time and seen from the increasing number of customers saving gold, the gold savings developed into a program that is not only aimed at the middle class but also aimed at the general community. Until now, gold saving has been run throughout PT. Pegadaian Branch and Unit as in PT. Pegadaian Branch of Pekanbaru City Panam Riau Province.The results of this study explain that the increasing number of customers saving gold at PT. Pegadaian (Persero) Pekanbaru Panam Branch, Riau Province, is due to the efforts of PT. Pegadaian in recruiting potential customers. One of the efforts and ways to do is to run a process of persuasive communication. The success of the persuasive process can be seen based on the characteristics of communicators PT. Pegadaian (Persero) in recruiting prospective customers, the form of persuasive message submitted by PT. Pegadaian (Persero) in recruiting potential customers and communication media used by PT. Pegadaian (Persero) in recruiting potential customers.Keywords: Communication Persuasive, Marketing Communications, Golden Saving